The two faces of sustainability : Fuzzy evaluation of sustainable development. - Cornelissen, T. (Wageningen University & Research, 2003)
An evaluative framework of sustainable development operates at both the production system level and the society level: objective information gathered at the production system level is given subjective meaning at the society level. The evaluative framework constitutes a complete cycle to monitor sustainable development: Phases 1 through 4 establish evaluative conclusions, and Phase 5 closes the cycle by acting upon the conclusions. Emphasis in this thesis is on methodological aspects to identify (Phases 1 through 3) and interpret (Phase 4) sustainability criteria. The objectives of this study were to construct a support to identify appropriate sustainability criteria, and to obtain relevant information with respect to sustainable development; and to construct a method to interpret this information, and to draw evaluative conclusions about sustainable development. Based on Koestler's metaphor of the Janus-faced holon, the «two faces of sustainability» provide a two-way perspective by integrating ecocentric and anthropocentric rationales on sustainability in a system imperative and a societal imperative. These two imperatives of sustainability identify common ground for sustainable development that allows proper identification of sustainability criteria. If appropriate sustainability criteria have been identified, then giving meaning to the information obtained from sustainability criteria, by way of measuring or observing sustainability indicators, is the next phase in drawing conclusions about sustainable development. Fuzzy set theory was suggested as a formal mathematical basis to support Phase 4. The main body of research presented in this thesis deals with the feasibility of fuzzy set theory to interpret and integrate available information. Fuzzy models can interface information between the society level and the production system level, because linguistic variables provide a bridge between subjective interpretation of objective measurements. If expert knowledge is thoughtfully applied to construct both the essential membership functions and fuzzy rule bases, then fuzzy models can draw valid evaluative conclusions with respect to sustainable development. The evaluative framework of sustainable development that identifies sustainability criteria on the basis of the point of view provided by the two faces of sustainability, and that gives meaning to sustainability criteria on the basis of fuzzy evaluation, provides a novel and valuable contribution to the sustainability debate.